Keabsahan Kontrak Elektronik Dalam Layanan Pinjaman Online yang Menggunakan Identitas Pihak Ketiga - Laksono, Fajar Galuh; Risqullah, Arya Razan; Anggriani, Reni (Universitas Muhammadiyah Yogyakarta, 2025)
This research discusses the validity of electronic contracts in online loan services that use third-party identities without permission. This phenomenon is rampant with the development of digital technology and the ease of access to application-based financial services. The main issue in this research is how the legal review of the validity of electronic contracts in cases of identity theft and how legal protection for victims is addressed. This research uses a normative juridical method with a legislative and conceptual approach. The research results show that electronic contracts made using a third party's identity without valid consent do not meet the elements of agreement as regulated in Article 1320 of the Civil Code, thus the contract can be considered null and void by law. Additionally, legal protection for victims of identity theft in online loan services is still weak, considering the absence of specific regulations that detail mechanisms for protection and recovery for victims. This research uses a normative legal method, namely an approach that is based on the analysis of regulations, legal doctrine, and relevant case studies. Therefore, there is a need to strengthen regulations and enhance the role of fintech providers in ensuring the validity of user identities to create legal certainty and fair protection for all parties.